Altered Distribution of Circulating T Follicular Helper-Like Cell Subsets in Rheumatoid Arthritis Patients - Su, Rui; Wang, Yanyan; Hu, Fangyuan; Li, Baochen; Guo, Qiaoling; Zheng, Xinyu; Liu, Yue; Gao, Chong; Li, Xiaofeng; Wang, Caihong (Frontiers in Medicine, 2021)
Objective: Recent studies on follicular regulatory T (Tfr) and follicular helper T (Tfh) cells suggested that they may participate in the pathogenesis of rheumatoid arthritis (RA). Here, we examined Tfr-like and Tfh-like cells and their subsets in RA and assessed the correlations between these subsets with B cells and cytokines related to the pathogenesis of RA and their clinical significance. Methods: The study population consisted of 18 healthy controls and 47 RA patients (17 new-onset, 57.00 ± 11.73 years; 30 treated RA patients, 57.56 ± 1.97 years). Disease activity scores in 28 joints were calculated. The positive rates of rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP) were 82.9% and 89.4%, respectively. Cell subsets were analyzed using flow cytometry, and serum cytokine levels were measured using cytometric bead array. Results: Tfh-like and PD-1+Tfh-like cells were elevated and the distribution of Tfh-like cell subsets was altered, with increased Tfh17-like and Tfh1/17-like cells in RA patients. The receiver operating characteristics curves for Tfh-like, Tfh17-like, Tfh1/17-like, and PD-1+ Tfh-like cells indicated improved RA diagnostic potential. RA patients had decreased regulatory T (Treg), Tfr-like, and memory Tfr-like (mTfr-like) cells and increased Tfh-like/Treg, Tfh-like/Tfr-like, and Tfh-like/mTfr-like cell ratios. Tfh-like cells and their subsets, including Tfh1-like, Tfh2-like, Tfh1/17-like, and PD-1+ Tfh-like cells, were positively correlated with B cells. Tfh-like/Treg, Tfh-like/Tfr-like, and Tfh-like/mTfr-like cell ratios were positively correlated with B cells in new-onset RA. Interleukin (IL)-2, IL-4, IL-17, interferon-γ, and tumor necrosis factor-α were positively correlated with Tfr-like and mTfr-like cells. IL-2 and IL-10 were positively correlated with Tfh-like and Tfh2-like cells. IL-4 was positively correlated with Tfh-like cells. Conclusions: Tfh-like and PD-1+ Tfh-like cells are increased, whereas Treg, Tfr-like, and mTfr-like cells are decreased in RA, leading to imbalance in Tfh-like/Treg, Tfh-like/Tfr-like, and Tfh-like/mTfr-like cell ratios. Tfh-like cells and a portion of their subsets as well as Tfh-like/Treg, Tfh-like/Tfr-like, and Tfh-like/mTfr-like cell ratios are closely related to B cells. Dysfunction of cell subsets leads to abnormal levels of cytokines involved in the pathogenesis of RA. The altered distributions of Tfh-like cell subsets, especially Tfh1/17-like cells, represent potential therapeutic targets for treatment of RA.